Proses murabatah al-nafs menurut perspektif al-Ghazali bagi membangunkan individu seimbang dan holistik - Mohd Fakharuddin, Fathiyah; Suhid, Asmawati (Middle Eastern Muslim Graduates Association Press, 2016)
Al-nafs or soul is an important element in one’s self. Al-nafs commonly referred as a spiritual element that complement the physical element of a human. Al-Ghazali was among the scholars that greatly discussed on al-nafs or soul and the process to develop the soul. This paper focused on the process of murabatah al-nafs stated by al-Ghazali to ensure the holistic personal development. The process of murabatah al-nafs is required to develop the soul and have a peaceful soul or nafs mutmainnah. This murabatah al-nafs process encompasses of six stages. The six stages are musyaratah, muraqabah, muhasabah, mu`aqabah, mujahadah and mu`atabah. The stage of musyaratah refers to the process of determining goals that to be achieved by individual’s soul. Muraqabah is a stage that include the process of sensing Allah’s observation towards an individual. The next stage is the stage of muhasabah whereby the individual reflects on his future and past actions. After the process of muhasabah, the individual is recommended to do mu`aqabah process that refers to the act of condemning the lack of deeds and offenses committed. The following stage is the stage of mujahadah. Mujahadah refers to the determination of an individual doing deeds and avoiding sins. The last stage of this murabatah al-nafs process is the stage of mu`atabah. Mu`atabah refers to the process of individual reminding himself and critised his wrongdoings. As a conclusion, these six stages in the process of murabatah al-nafs can served as an effective mechanism to develop a balanced and holistic individual. This process can be applied in formal education at school setting or informal education at homes.